1991
DOI: 10.1002/jemt.1060190209
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the aging human testis

Abstract: The ultrastructure of the progressive testicular involution with advancing age in men is reviewed. There is no definite age at which testicular involution begins, and the onset and severity of testicular lesions are subjected to pronounced individual variations. Hormone studies also indicate great individual variations, and subtle changes in both the testis and the pituitary develop progressively with age. Testicular size, sperm quality, and numbers of all germ cell types, Sertoli cells, and Leydig cells decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
85
0
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(104 citation statements)
references
References 87 publications
12
85
0
2
Order By: Relevance
“…This effect was proposed previously in rats exposed to methyl mercury, where spermatogenic distortion was mediated through affected Sertoli cells [23]. However, the apparent sensitivity of Sertoli cells to nicotine does not exclude the possibility that germinal cells are the target, as spermatocyte and spermatid susceptibility (as shown in the present rat testis) to other toxic materials was also reported [24]. In the present study, the considerable electron-dense deposits in spermatids con®rm germ-cell sensitivity to nicotine.…”
Section: Discussionsupporting
confidence: 72%
“…This effect was proposed previously in rats exposed to methyl mercury, where spermatogenic distortion was mediated through affected Sertoli cells [23]. However, the apparent sensitivity of Sertoli cells to nicotine does not exclude the possibility that germinal cells are the target, as spermatocyte and spermatid susceptibility (as shown in the present rat testis) to other toxic materials was also reported [24]. In the present study, the considerable electron-dense deposits in spermatids con®rm germ-cell sensitivity to nicotine.…”
Section: Discussionsupporting
confidence: 72%
“…The progression of fibrosis with age causes separation of the germinal epithelium from the blood supply. The development of tubular involution with age is thought to have an essential role in testicular atrophy [12].…”
Section: The Effect Of Aging On Sexual Organsmentioning
confidence: 99%
“…In addition, Leydig cells may also contain an underdeveloped endoplasmic reticulum (ER) and a number of lipofuscin granules. At later stages of dedifferentiation, the nucleolus shrinks or disappears completely [12].…”
Section: The Effect Of Aging On Sexual Organsmentioning
confidence: 99%
“…Wide intercellular spaces contained cellular debris and nearly absent spermatogenic cells leaving their location on Sertoli cells. Some authors suggested that vacuolation of Sertoli cells is attributed to the These ultrastructural changes are found in progressive testicular involution with advancing age in men, which may be related to hormonal changes found in old age [44]. These findings are also detected in rats treated by well-established antipsychotic, lithium carbonate [45].…”
Section: Discussionmentioning
confidence: 99%